2016
DOI: 10.1159/000448957
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, Bacterial Translocation, and Interactions with Diet: Pathophysiological Links between Major Depressive Disorder and Non-Communicable Medical Comorbidities

Abstract: Background: Persistent low-grade immune-inflammatory processes, oxidative and nitrosative stress (O&NS), and hypothalamic-pituitary-adrenal axis activation are integral to the pathophysiology of major depressive disorder (MDD). The microbiome, intestinal compositional changes, and resultant bacterial translocation add a new element to the bidirectional interactions of the gut-brain axis; new evidence implicates these pathways in the patho-aetiology of MDD. In addition, abnormalities in the gut-brain axis are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 194 publications
(221 reference statements)
1
144
1
12
Order By: Relevance
“…Therapeutic strategies for altering the gut microbiome include changes in diet, probiotics, and prebiotics. In this line, probiotics are being tested as procognitive agents in other psychiatric conditions given their antiinflammatory properties (Slyepchenko et al, 2017), so they appear as a new potential treatment to examine in bipolar illness.…”
Section: Future Clinical Directionsmentioning
confidence: 99%
“…Therapeutic strategies for altering the gut microbiome include changes in diet, probiotics, and prebiotics. In this line, probiotics are being tested as procognitive agents in other psychiatric conditions given their antiinflammatory properties (Slyepchenko et al, 2017), so they appear as a new potential treatment to examine in bipolar illness.…”
Section: Future Clinical Directionsmentioning
confidence: 99%
“…increased permeability), endogenous LPS can "leak" across defective tight junctions of the intestines into the body's circulation, which results in an immune response that can spur neuroinflammation and neuropsychiatric illness 72  LPS can disturb previously primed microglia to exacerbate neuroinflammation and prompt disease 56  Serum LPS levels emanating from damaged intestinal walls found to correlate with disease severity for neurodegenerative disorders in human patients (e.g., Parkinson's)…”
Section: Box 1: Key Points Related To Lipopolysaccharide (Lps)mentioning
confidence: 99%
“…Others studies demonstrated that the microorganisms from the phylum Firmicutes are increased and there is a great decrease in bifidobacteria [40][41][42]. Weight changes of NC, OC groups and mice given with the different dietary supplements OM, OY and OPY were determined weekly during 60 days.…”
Section: Resultsmentioning
confidence: 99%